Epstein-barr virus infection and single nucleotide Polymorphisms in the promoter region of interleukin 10 gene in patients with Hodgkin lymphoma - Da Silva, Glenda Nicioli; Bacchi, Maura Moscardi; Rainho, Claudia Aparecida; Oliveira, Deilson Elgui de [UNESP] (College Amer Pathologists, 2007)
Context. - Hodgkin lymphoma is a neoplastic disease in which the immune system plays a major role in its pathogenesis. Interleukin 10 ( IL-10), an immunosuppressive cytokine actively produced in patients with Hodgkin lymphomas, favors the survival of the Hodgkin/Reed-Sternberg cells. Individual variations in IL-10 levels may be due, in part, to the presence of single nucleotide polymorphisms in the IL10 gene promoter.Objective. - To evaluate whether particular single nucleotide polymorphisms in the IL10 gene are found more frequently in Hodgkin lymphoma cases associated with Epstein-Barr virus infection.Design. - the identification of single nucleotide polymorphisms at positions -1082 and -819/-592 in the IL10 gene was performed by polymerase chain reaction and restriction length fragment polymorphisms analysis in 65 cases of Hodgkin lymphoma and 50 cases of reactive benign follicular lymphoid hyperplasia ( non-Hodgkin lymphoma control group).Results. - the frequency of the genotype GG at position -1082 was found to be significantly higher in patients with Epstein-Barr virus-positive Hodgkin lymphoma compared with Epstein-Barr virus-negative cases.Conclusions. - the results suggest that the presence of specific single nucleotide polymorphisms in the IL10 gene, notably those associated with high IL-10 production, may play a role in the susceptibility to Epstein-Barr virus -positive Hodgkin lymphoma development.